Determinan Risiko Pembiayaan Bagi Hasil Pada Bank Umum Syariah di Indonesia - Ramli, Rosmini; Desmiza, (Al-Mashrafiyah: Jurnal Ekonomi, Keuangan, dan Perbankan Syariah, 2022)
This study aims to determine the effect of bank-specific and macroeconomic factors on financing risk for Islamic Commercial Banks. The financing risk in the previous study focused more on the overall financing risk involving the bank's internal and macroeconomic aspects, either separately or together. There is still limited research that examines financing specifically, both the use of these two factors separately or together, especially on the risk of profit-sharing financing. This study will complement the literature on the above issues. This study uses quantitative methods with panel data regression analysis using quarterly financial ratio data from Islamic Commercial Banks in Indonesia for the period 2012-2020. The results showed that the dominant bank-specific factor influenced the risk of profit-sharing financing, while the macroeconomic factor was only inflation which showed a significant effect.